Climate and Its Impact on Bioclimatic Comfort in Babylon Governorate - Rouaa Ali Mahdi; Akram Hasan Mutlag (Zanco Journal of Human Sciences, 2025)
The research aimed to show the effect of climate on bioclimatic comfort in Babil Governorate, as the most important climatic characteristics affecting bioclimatic comfort were used and relied on many statistical equations that explain the extent of the feeling of comfort, including the temperature and humidity index coefficient of the scientist Tom, the equivalent temperature equation, the stress index, and the wind cooling equation, In addition to using modern geographical techniques (GIS),the importance of the research is evident in employing comfort indicators in any month of the year, relying on climate characteristics to clarify comfort levels in the study area, and the descriptive and analytical approach was adopted, In addition to the quantitative method that is compatible with the data obtained from government publications, the research contributes to providing information to planners and investors in all areas related to human comfort, and helps the people of society themselves in determining the best times for rest and the tools to help lighten the atmosphere during discomfort.